(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The article examines the problem of the author’s position and the dialogic nature of a literary text in modern literary studies. The research analyzes theoretical approaches to the interpretation of authorial consciousness within the structure of a literary work. Particular attention is paid to the concept of dialogism, which implies the interaction of different voices within the literary text. The author’s position is manifested through the system of images, compositional structure and linguistic means of the work. The dialogic nature of literary texts contributes to a deeper understanding of the author’s idea and expands the possibilities of interpretation.